Certain Subclasses of Bi-Close-to-Convex Functions Associated with Quasi-Subordination - Gurmeet Singh; Gurcharanjit Singh; Gagandeep Singh (Abstract and Applied Analysis)
In the present investigation, we introduce certain new subclasses of the class of biunivalent functions in the open unit disc U=z:z<1 defined by quasi-subordination. We obtained estimates on the initial coefficients a2 and a3 for the functions in these subclasses. The results present in this paper would generalize and improve those in related works of several earlier authors.